LERMONTOV'S IMPACT ON 19TH CENTURY RUSSIAN LITERATURE AND BEYOND - Ruzibayeva Aziza Kahramanovna (Western European Studies, 2023)
This paper explores the profound impact of Mikhail Lermontov on 19th-century Russian literature and its enduring influence beyond that era. Lermontov, a key figure of the Russian Romantic movement, not only contributed significantly to the literary landscape of his time but also left an indelible mark on subsequent generations of writers. The analysis delves into Lermontov's unique literary style, thematic concerns, and the socio-cultural context of his works, examining how these elements shaped the literary trends of the 19th century and continued to resonate in the broader scope of Russian literature. The study also investigates the ways in which Lermontov's influence transcended national borders, impacting literary movements and authors far beyond the confines of 19th-century Russia.
Keywords: Mikhail Lermontov; 19th-century Russian literature; Russian Romantic movement